Book review: A. R. Venkatachalapathy, Who Owns That Song? The Battle for Subramania Bharati's Copyright. (April 2021) - Sethi, Devika
A. R. Venkatachalapathy, Who Owns That Song? The Battle for Subramania Bharati's Copyright . New Delhi: Juggernaut, 2018, 192 pp.